1989
DOI: 10.1016/s0006-3495(89)82798-5
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis intermediates of the artificial visual pigment cis-5,6-dihydro-isorhodopsin

Abstract: The photolysis intermediates of an artificial bovine rhodopsin pigment, cis-5,6-dihydro-isorhodopsin (cis-5,6,-diH-ISORHO, lambda max 461 nm), which contains a cis-5,6-dihydro-9-cis-retinal chromophore, are investigated by room temperature, nanosecond laser photolysis, and low temperature irradiation studies. The observations are discussed both in terms of low temperature experiments of Yoshizawa and co-workers on trans-5,6-diH-ISORHO (Yoshizawa, T., Y. Shichida, and S. Matuoka. 1984. Vision Res. 24: 1455-1463… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…These retinal analogues cause an altered photoreaction (Albeck et al 1989;Shichida et al 1981;Ganter et al 1989). In 9-H-rhodopsin, transducin is activated to only a very limited extent .…”
Section: Introductionmentioning
confidence: 99%
“…These retinal analogues cause an altered photoreaction (Albeck et al 1989;Shichida et al 1981;Ganter et al 1989). In 9-H-rhodopsin, transducin is activated to only a very limited extent .…”
Section: Introductionmentioning
confidence: 99%
“…The photobleaching process of rhodopsin has been investigated using retinal analogs that contained an extra ring between C 10 and C 13 , making retinal non-isomerizable around the 11-cis double bond (7)(8)(9)(10)(11)(12)). An artificial visual pigment with restricted C 9 -C 11 motion forms normal photolysis intermediates (13), suggesting an importance of C 11 ϭC 12 bond isomerization in the activation of Rho.…”
mentioning
confidence: 99%
“…An artificial visual pigment with restricted C 9 -C 11 motion forms normal photolysis intermediates (13), suggesting an importance of C 11 ϭC 12 bond isomerization in the activation of Rho. More recently, it was reported that after photoisomerization, the ␤-ionone ring of the chromophore moves to a new position during the transition to Meta II (7).…”
mentioning
confidence: 99%
“…On a nanosecond time scale, Batho is in equilibrium with the blue-shifted intermediate (BSI), which decays to form lumirhodopsin (Lumi), an intermediate with a lifetime of microseconds. [13][14][15][16] The dynamic details of the process has been well-studied by previous molecular dynamics simulations. 36,38,49 In this work, we evaluated the contributions of each residues in terms of EAWs during the transition from Batho to BSI, which is the preliminary step towards a thorough understanding of the whole photo-activation process and also of profound implications for protein-ligand interactions.…”
mentioning
confidence: 99%